Analisis Faktor-faktor Munculnya Word of Mouth Mempengaruhi Keputusan Berkuliah di Universitas Teknologi Sumbawa - Koko Hermanto (Performa: Media Ilmiah Teknik Industri, 2021)
Many universities at the national and local levels have resulted in the emergence of competition between universities in obtaining prospective students. Therefore, universities have to show all their potential and advantages in every aspect, including the Universitas Teknologi Sumbawa (UTS), even though it is ranked in the top five universities in West Nusa Tenggara. This study aims to analyze the factors of service quality, customer satisfaction, and experiential marketing that UTS has implemented has influenced the marketing of word-of-mouth techniques optimally or not in attracting prospective students to study at UTS. This study's results can provide an overview for UTS in providing services to students with administrative services carried out by staff and lecturers in teaching. This study's population was UTS students who were still actively studying with a research sample of 165 students. In order to achieve the objectives of this study, questionnaire data from respondents were tested by using the Structural Equation Model (SEM) method using LISREL 8.8 software. The research results obtained a structural equation: word of mouth = -21 × service quality + 0.3 × customer satisfaction + 0.71 × experiential marketing with R2 = 71%. The hypothesis testing results show that of the three variables, only experiential marketing variables have a positive and significant effect on UTS students' word of mouth decision.